Creencias que tienen docentes de matemáticas en formación sobre la solución de problemas. un estudio de casos en la universidad Antonio Nariño (2017)
The purpose of this document is to present the information carried out in the second semester of 2016, in the field of Teaching Practice I of the sixth semester students of the Bachelor's Degree in Mathematics at the Antonio Nariño University, regarding the beliefs that are taken regarding the solution of problems in mathematics in school education.